1987
DOI: 10.1128/mcb.7.11.4075
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous expression of two P-glycoprotein genes in drug-sensitive Chinese hamster ovary cells.

Abstract: Overexpression of P-glycoprotein is characteristic of multidrug-resistant cells. We analyzed four Pglycoprotein transcripts that are simultaneously expressed in a drug-sensitive Chinese hamster ovary cell line. We concluded that these transcripts are encoded by two distinct members of a P-glycoprotein multigene family, each of which has two alternative polyadenylation sites. A comparison of the two hamster sequences with the single reported human and mouse P-glycoprotein cDNA sequences demonstrates that P-glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…A central issue in understanding the normal functions of the P-glycoprotein has been the development of data indicating that the gene encoding the P-glycoprotein is a member of a multigene family (11,15,18,30). Probes from the amplified DNA domain in multidrug-resistant cell lines cross-hybridized to multiple genomic sequences (16,25) and identified two homologous but distinct mouse cDNAs (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A central issue in understanding the normal functions of the P-glycoprotein has been the development of data indicating that the gene encoding the P-glycoprotein is a member of a multigene family (11,15,18,30). Probes from the amplified DNA domain in multidrug-resistant cell lines cross-hybridized to multiple genomic sequences (16,25) and identified two homologous but distinct mouse cDNAs (17).…”
mentioning
confidence: 99%
“…Drug-resistant cell lines selected by stepwise selection using a single cytotoxic compound are often crossresistant to a broad spectrum of structurally and functionally unrelated chemotherapeutic agents (5,6,9,21,23). Multidrug-resistant cultured cell lines express increased levels of the P-glycoprotein (22), a 170-kilodalton membrane glycoprotein encoded by a gene termed mdr (16,24,25) or pgp (11). P-glycoprotein appears to cause multidrug resistance via an energy-dependent drug efflux mechanism (10,26).…”
mentioning
confidence: 99%
“…Hence, only class 1 includes the drug-transporting P-glycoproteins or multidrug transporters which are the focus of this review. The human MDR1 (Chen et al, 1986), the mouse mdr3 (or mdr1a) (Devault and Gros, 1990; and mdr1 (or mdr1b) (Gros et al, 1986b), the hamster pgp1 and pgp2 (Endicott et al, 1987;Gros et al, 1986c), and the rat pgp1 and pgp2 (or mdr1b) gene products (Deuchars et al, 1992;Silverman et al, 1991) all belong to this class, while non drug-transporting P-glycoproteins, such as the human MDR2, or an alternative splice form thereof referred to as MDR3 (Schinkel et al, 1991;Van der Bliek et al, 1987), the mouse mdr2 (Buschman et al, 1992;Gros et al, 1988), the hamster pgp3 (Endicott et al, 1991), and the rat mdr2/mdr3 (Brown et al, 1993;Furuya et al, 1994) gene products belong to class 2 (which sometimes is also described as class 3). Class 2 mdr gene products are primarily expressed in the liver bile canaliculi (Buschman et al, 1992;CordonCardo et al, 1990;Smit et al, 1994;van der Valk et al, 1990) and analyses of mdr2 knock-out mice have indicated that class 2 P-glycoproteins represent phosphatidylcholine transporters (Smit et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Transfection experiments (8,16,36) have demonstrated that overproduction of P-glycoprotein is sufficient to cause MDR. Analyses of partial and full-length cDNAs encoding P-glycoprotein from hamster (11,12), mouse (15,17), and human (3, 37; A. M. van der Bliek, P. M. Kooiman, C. Schneider, and P. Borst, Gene, in press) cells have shown that P-glycoprotein is a highly conserved protein which appears to be tandemly duplicated. Each duplicated half consists of six potential membrane-spanning regions and a putative nucleotidebinding site, features compatible with the proposed role of P-glycoprotein as an energy-dependent pump (3,12,15).…”
mentioning
confidence: 99%
“…A family of closely related genes, referred to as pgp genes in hamsters (11) and as mdr genes in mice and humans (3,15,17,37), encodes P-glycoprotein (29). These genes are frequently differentially amplified in cell lines selected for resistance to different drugs (7,29,32).…”
mentioning
confidence: 99%